Inpatient Coding System and Opportunities for Documentation Optimization: An Interactive Session for Internal Medicine Residents - Lindsey Jordan Gay; Doris Lin; Ziba Colah; Glynda Raynaldo (Association of American Medical Colleges, 2022)
Introduction The Inpatient Prospective Payment System, the framework for categorization of admissions, is based upon physician documentation leading to International Classification of Diseases, Tenth Revision code generation and Medical Severity Diagnosis-Related Group (MS-DRG) assignment. In this curriculum, we introduced internal medicine residents to this inpatient coding framework and its effects on hospital quality metrics and reimbursement. We focused on educating learners about the importance of physicians being proficient in providing thorough and specific clinical documentation to produce appropriate DRG assignment. Methods Internal medicine residents participated in a 90-minute session that introduced the basic framework of inpatient coding, discussed effects of physician documentation on hospital quality metrics and reimbursement, and provided tips on opportunities for documentation improvement. In an interactive learning activity, residents were presented with clinical vignettes and earned reimbursement based on their documentation of appropriate diagnoses. Each scenario was followed by clinical definitions and actionable documentation recommendations for common diagnoses. Materials included a PowerPoint presentation, clinical vignettes, sample teaching points, and a rubric to calculate estimated reimbursement. Results Prior to the session, 38% of learners were confident in their understanding of how documentation affects hospital reimbursement, which improved to 90% postsession. Learners reported improvement in their knowledge of documentation requirements for all targeted diagnoses. Discussion This interactive curriculum improved resident knowledge of the inpatient coding system and documentation requirements for common diagnoses and addressed a deficiency in residency education on a topic of significant importance for the success of hospital systems.